INFLUENCE OF THE PHYSICAL STATE OF ENDOTOXIC PREPARATIONS ON DERMAL TOXICITY - Roberson, Bob S. (1962)
Roberson, Bob S. (University of North Carolina, Chapel Hill) and William J. Cromartie. Influence of the physical state of endotoxic preparations on their dermal toxicity. J. Bacteriol. 84:882–887. 1962.—Studies were performed with various preparations of endotoxin from Escherichia coli to test for a possible relation between the physical state or degree of aggregation of the toxin and dermal toxicity. Endotoxic fractions were prepared by enzymatic and physical dissolution of cell walls, phenol extraction, and ether extraction. A comparison of the toxic effects of the different preparations after a single intradermal injection into rabbits demonstrated that the degree and duration of the inflammatory response was influenced significantly by the physical state of the preparation. In addition, the least active material, the aqueous ether extract, was treated so as to yield three preparations differing only in the degree of aggregation. Dermal titration of these preparations suggests that a departure from an optimal range of particle size results in a diminished capacity of endotoxin to induce the acute and protracted manifestations of dermal response.